ÇEKÜL Foundation and Digital City Archive - Ayşen Kılıç Özarslantürk (Türk Kütüphaneciliği)
The Foundation for the Protection and Promotion of the Environmental and Cultural Heritage (ÇEKÜL) has undertaken conservation work in the fields of natural, historical and cultural heritage in city-basin-regional-country scales. In order to protect the archival materials that have emerged / are emerging in this framework, and to expand the access network, ÇEKÜL started digitization projects with “The City Archive Digitization Project.” Following two years of work, the “Digital City Archive” was released.